2020
DOI: 10.11604/pamj.supp.2020.35.23121
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in the COVID-19 pandemic control preparedness in a developing economy

Abstract: Adequate preparation for highly pathogenic infectious disease pandemic can reduce the incidence, prevalence and burden of diseases like COVID-19 pandemic. An antidote to the spread of the disease is adequate preparation for its control since there is no proven curative measure yet. Effective management of identified cases, social distancing, contact tracing and provision of basic infrastructure to facilitate compliance with preventive measures, testing are proven management strategies. Although these measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Among racialized Americans, Egelko et al (2020) noted that distrust in the healthcare system and the state was present due to racist treatment that had and continued to exist within them, and the ongoing role these institutions had in perpetuating health inequities. Similarly, immigrants lacking legal status were also hesitant to receive a test, as there was a fear that the government may use personal information to ensure immigration enforcement [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among racialized Americans, Egelko et al (2020) noted that distrust in the healthcare system and the state was present due to racist treatment that had and continued to exist within them, and the ongoing role these institutions had in perpetuating health inequities. Similarly, immigrants lacking legal status were also hesitant to receive a test, as there was a fear that the government may use personal information to ensure immigration enforcement [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors argued that using pre-existing or repurposing older networks as platforms for sharing preliminary information and giving access to real-time data before they are available in scientific or medical communities is a crucial step to take when preparing for further pandemics. Jegede et al [ 25 ] argued that a framework and ethical guidelines are extremely valuable during a pandemic; building on the discourse around contextually sensitive measures, the authors showed that ethically sensitive communication and appropriate countermeasures had a positive impact on the public in the Global South.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly , our findings indicated the important role of GEFs in enhancing public trust in and compliance with the government. Therefore, it is critical that the government should always be well-prepared and anticipate possible scenarios for the potential risks of the current pandemic and future public health crises (Jegede et al , 2020). Lack of sufficient preparedness may lead to ineffectiveness in containing the pandemic, which can thereby erode PTG, and thus, reduce their compliance with the government (Orfali, 2021).…”
Section: Practical Implicationsmentioning
confidence: 99%